What the course of bioethics? - Almeida, Marcos de (2012)
The author summarizes his increasing worries on the next steps of bioethical thinking and emphasizes the strong need to keep in pace with the legitimate problems of our world, instead of the apparent atractiveness of some colourful, but maybe futile, topics.